Breast Massage Using Lavender Oil To Increase Breast Milk Production Of Breastfeeding Mothers - Christina Elisabeth Tampubolon; Margono Margono; Yuliantisari Retnaningsih (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Exclusive breastfeeding is recommended for at least 6 months. One of the leading factors that causes breastfeeding mothers experience problems in offering exclusive breastfeeding is the insufficient production of breast milk. Breast massage by utilizing soothing lavender oil is a method to boost breast milk production and also increase the production of oxytocin Hormones and smoothen the flow reflex.Purpose of this study is to analize effect of breast massage using lavender oil to breast milk production. Methods: This study uses a quasi experimental type with a before and after design with control group. The population of the research is breastfeeding mothers in the working area of ​​Local Health Center of Pleret, involving 36 samples of breastfeeding mothers. Sampling was collected using purposive sampling technique with worksheets monitor the frequency baby's urination, baby's weight, and sleeping duration of the baby. Data analysis used paired test and independent test with computerized program. Results: The increase in breast milk production using lavender oil and coconut oil shows that the p-value is 0.000. The effect of the amount of breast milk production using lavender oil and coconut oil in breast massage shows that the p-value is 0.000. Conclusion: There is found was a significant (p-value 0.000) an effect of lavender oil in breast massage on milk production for breastfeeding mothers.